2019
DOI: 10.1002/cbic.201800585
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Cellular Redox‐Control System for Activatable Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) has been successfully used to treat a variety of cancers. However, one drawback has been the adverse side effects experienced by patients during therapy, as a result of the destruction of normal tissues upon irradiation. Herein, we describe the design, synthesis and characterisation of a photosensitiser to overcome this issue that, in addition to light, is also dependent on the overactive redox system present in cancer cells for its activation. Our probe consists of the photosensitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…In contrast to our results, Gharibi et al [69] recently demonstrated increased accumulation of flavonoids and expression of flavonoid biosynthesis genes in Achillea pachycephala after prolonged exposure to drought; the overall effect enhanced oxidative stress due to the increased accumulation of ROS like H 2 O 2 . Under stress conditions, the accumulation of secondary metabolites helps plants to modulate their response mechanisms as these substances act as key signaling components [71,72].…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Gharibi et al [69] recently demonstrated increased accumulation of flavonoids and expression of flavonoid biosynthesis genes in Achillea pachycephala after prolonged exposure to drought; the overall effect enhanced oxidative stress due to the increased accumulation of ROS like H 2 O 2 . Under stress conditions, the accumulation of secondary metabolites helps plants to modulate their response mechanisms as these substances act as key signaling components [71,72].…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolcontrasting
confidence: 99%
“…These metabolites have remarkable biological activities and are often exploited as medicinal and food ingredients for therapeutic, aromatic, and culinary purposes [68]. Increased accumulation of secondary metabolites prevents the oxidative effects of drought stress on the membrane structure and imparts greater pharmacological properties to plants [69]. Drought stress influences the accumulation of key secondary metabolites, including phenols and flavonoids, in Amaranthus [70].…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolmentioning
confidence: 99%
“…Possible side effects after PDT treatment include skin lesions and the ocular adverse events ( Vrouenraets et al, 2003 ; Huang, 2005 ). In order to improve patient prognosis and enhance PDT response, activatable photosensitizers have been developed ( Li et al, 2017c ; Gharibi et al, 2019 ; Digby et al, 2020 ; Liu and Li, 2020 ; Sun et al, 2020 ; Yuan et al, 2020 ; Zheng et al, 2020 ). The activatable photosensitizer designs can be used as an “ON/OFF” switch controlling PDT for effective cytotoxic singlet oxygen generation in the tumor tissue in vivo .…”
Section: Novel Approaches To Improve Outcomementioning
confidence: 99%
“…Lastly, theranostic prodrugs providing both real‐time hNQO1 activity monitoring and anticancer drug release in a single molecule have also been reported . However, despite the diverse set of probes currently exploiting hNQO1, to date, there are no reports of an hNQO1‐targeted optical therapeutic that can be used for PDT . With this in mind, we sought out to develop the first activatable PS (aPS) targeting hNQO1.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] However,d espite the diverse seto fp robesc urrently exploitingh NQO1, to date, there are no reportso fa nh NQO1targeted optical therapeutic that can be used for PDT. [33][34][35][36][37][38] With this in mind, we sought out to develop the first activatable PS (aPS)t argeting hNQO1.…”
Section: Introductionmentioning
confidence: 99%